Analytical Solution of One-Dimensional Keller-Segel Equations via New Homotopy Perturbation Method (Contemporary Mathematics, 2024)
For solving a system of nonlinear partial differential equations (PDE) emerging in an attractor one-dimensional chemotaxis model, we used a relatively new analytical method called the new modified homotopy perturbation method (NMHPM). We use NMHPM for solving one-dimensional Keller-Segel models for different types. Some properties show biologically acceptable dependency on parameter values, and numerical solutions are provided. NMHPM’s stability and reduced computing time provide it with a broader range of applications. The algorithm provides analytical approximations for different types of Keller-Segel equations. Some numerical illustrations are given to show the efficiency of the algorithm.
Keywords: HPM; Keller-Segel model; systems of PDE chemotaxis; numerical solution